The European Commission: Appointment, preferences, and institutional relations - Stefan Napel; Mika Widgrén (The Research Institute of the Finnish Economy (ETLA), 2006)
The paper analyzes the appointment of the European Commission as a strategic game between members of the EU's Council of Ministers and the European Parliament. The focal equilibrium results in Commissioners that duplicate policy preferences of national Council representatives. Different internal decision rules still prevent the Commission from being a Council clone in aggregate. Rather, it is predicted that Commission policies are on average more in accord with the aggregate position of the Parliament than the Council. A data set covering 66 dossiers with 162 controversial EU legislative proposals passed between 1999 and 2002 is investigated to test this. In fact, the Council is significantly more conservative than Parliament and Commission; the latter two are significantly closer to each other than Council and Commission.
Keywords: C70; D71; H77; 330; European Commission; European integration; power; collective choice; Europäische Integration; EU-Staaten; Politische Entscheidung